Circularly polarized luminescent porous crystalline nanomaterials. Issue 4 (12th January 2022) - Zheng, Anyi; Zhao, Tonghan; Jin, Xue; Miao, Wangen; Duan, Pengfei
Abstract : An overview of generation, regulation and amplification of circularly polarized luminescence (CPL) in porous crystalline nanomaterials by direct synthesis, chirality induction or adaption, and symmetry breaking pathways. Abstract : Circularly polarized luminescence (CPL)-active materials have attracted exclusive attention because of their wide potential applications in low-power-consumption displays, encrypted information storage, chiroptical sensors, and so on. However, there is always a trade-off between the luminescence dissymmetry factor ( g lum ) and luminescence quantum yield, which are two critical parameters. Therefore, developing materials with both large g lum values and high luminescence efficiency is a key issue for constructing high-efficiency CPL materials. To date, chiral porous crystalline nanomaterials (PCNMs) including metal–organic frameworks (MOFs), porous organic-cages (POCs), metal–organic cages (MOCs), and supramolecular organic frameworks (SOFs), have shown excellent potential for solving this problem and achieving functional CPL-active materials. In this review, we will summarize several approaches for fabricating CPL-active PCNMs, such as direct synthesis, chirality induction, and symmetry breaking. Furthermore, with flexibly tunable structures and comprehensive host–guest chemistry, modulation and amplification of CPL can be achieved in these PCNMs. We would like to provide insight and perspective that PCNMs can act as an efficient platform in the CPL research field.